Implementasi Agile Governance dalam Meningkatkan Kualitas Pelayanan Publik: Studi Keterbatasan SDM di Kelurahan Meteseh Semarang - Dinda Permata Putri; Aris Toening Winarni; Permadi M; Djuriyah Djuriyah (Universitas 17 Agustus 1945 Semarang, 2026)
Public services at the sub-district level still face various obstacles, particularly limited human resources (HR), which impact the quality of services to the public. On the other hand, increasing public demands require sub-district governments to be more adaptive and responsive. This study aims to analyze the implementation of agile governance in improving the quality of public services under conditions of limited HR in Meteseh Sub-district, Semarang City. This study used a mixed methods approach with an explanatory sequential design. Quantitative data were collected through surveys of officials and service users, while qualitative data were obtained through in-depth interviews and institutional document reviews. Data analysis was conducted descriptively and thematically using triangulation techniques. The results indicate that limited HR impacts the speed and responsiveness of public services. However, good organizational adaptability and the partial application of agile governance principles can maintain the quality of public services in the good category. Work flexibility, internal collaboration, and digital adaptation are key supporting factors in mitigating the impact of limited HR. This study concludes that agile governance can be an effective alternative approach to improving the quality of public services at the sub-district level, especially under conditions of limited human resources.